Enabling Teacher Leadership through Educational Entrepreneurship - Nickel, Jodi; Webber, Charles F. (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
This article was developed following a ten-month case study that explored how teacher leadership was manifested in a K-12 independent school. The researchers then conducted an oral history dialogue with the school’s founder to understand how his vision influenced the establishment of this specialized school for students with learning disabilities and how that vision continues to shape the school. Five themes emerged from the oral history: 1) vision and need for a specialized school; 2) teacher knowledge and expertise; 3) relationship building and trust; 4) social and political acumen; and 5) independence to support innovation. These results highlight how educational entrepreneurship from those who are not educators can contribute to ameliorating educational challenges by establishing an environment where teacher leaders can thrive.